Effect of Ketamine/Propofol Admixture on Peri-Induction Hemodynamics: A Systematic Review and Meta-Analysis - Nathan J. Smischney; Mohamed O. Seisa; Allison S. Morrow; Oscar J. Ponce; Zhen Wang; Muayad Alzuabi; Katherine J. Heise; Mohammad H. Murad (Anesthesiology Research and Practice, 2020)
To evaluate the effectiveness of an admixture of ketamine and propofol on peri-induction hemodynamics during airway manipulation, we searched electronic databases of randomized controlled trials from January 1, 2000, to October 17, 2018. Trial screening, selection, and data extraction were done independently by two reviewers with outcomes pooled across included trials using the random-effects model. We included 10 randomized trials (722 patients, mean age of 53.99 years, 39.96% female). American Society of Anesthesiologists physical status was reported in 9 trials with classes I and II representing the majority. Ketamine/propofol admixture was associated with a nonsignificant increase in heart rate (weighted mean difference, 3.36 beats per minute (95% CI, −0.88, 7.60), I2 = 88.6%), a statistically significant increase in systolic blood pressure (weighted mean difference, 9.67 mmHg (95% CI, 1.48, 17.86), I2 = 87.2%), a nonsignificant increase in diastolic blood pressure (weighted mean difference, 2.18 mmHg (95% CI, −2.82, 7.19), I2 = 73.1%), and a nonsignificant increase in mean arterial pressure (weighted mean difference, 3.28 mmHg (95% CI, −0.94, 7.49), I2 = 69.9%) compared to other agents. The risk of bias was high and the certainty of evidence was low. In conclusion, among patients undergoing airway manipulation and needing sedation, the use of a ketamine/propofol admixture may be associated with better hemodynamics compared to nonketamine/propofol sedation. This trial is registered with CRD42019125725.